Finslerian Extension of Special Relativity and the Possibility of Experimental Search for Local Space Anisotropy - Bogoslovsky, G. Yu. (New Trends in Physical Science Research Vol. 1, 2022)
The impact of local space anisotropy on the transverse Doppler effect is examined. Two types of laboratory experiments aimed at seeking and measuring the local space anisotropy are proposed. In terms of the conventional special relativity, which treats 3D space to be locally isotropic, all these experiments are of the type of “null-experiments”. In the first-type experiments, a feasible Doppler shift of frequency is measured by the Mossbauer effect, with the Mossbauer source and absorber being located at two identical and diametrically opposed distances from the center of a rapidly rotating rotor, while the \(γ\)-quanta are recorded by two stationary and oppositely positioned proportional counters. Either of the counters records only those \(γ\)-quanta that passed through the absorber at the moment of the passage of the latter near a counter. The second-type experiments are made using the latest radio physics techniques for generating monochromatic oscillations and for recording weak signals. The effect expected due to space anisotropy consists in frequency modulation of the harmonic oscillations coming to a receiver that rotates at a constant velocity around the monochromatic wave emitter. In this case the modulation depth proves to be proportional to the space anisotropy magnitude.